Importance of uniformity coefficients in machine-assisted agricultural operations (technical note) - Gomez-Calderón, Natalia (2022)
The efficiency of mechanized agricultural work affects the general yield of crops and the uniformity of production, determining variables in the adequate definition of differentiated management areas. Implement consistency tests impact implement purchasing and implement management decisions. The objective of this work is to promote the efficient use of agricultural machinery in the field and to evaluate agricultural operations for the proper use of production resources. Uniformity coefficients of the work carried out with each of the implements tested were determined, as well as other operative variables that influence their performance. The most uniform tasks are those carried out with vertical tillage implements (CU > 80%), although they demand more power to break the soil structure, the volumetric seeder is more uniform at low speeds (CU = 86.73%) and the sprayer presented more homogeneous applications at low operating pressures (CU = 98%). The uniformity measurements and calibration activities of the implements allowed identifying critical points in the machinery, and substantiating the importance of determining them for the continuous improvement of agricultural operations aimed at achieving homogeneous crop yields.